Factors affecting breasrt milk in post partum mothers at atikah sipolu clinic, panyabungan district, Mandailing Natal - Helmi wardah Nasution; Ferika Desi (Institute of Computer Science (IOCS), 2023)
Every year the number of babies and toddlers due to malnutrition continues to increase. Breast milk are milk deposition due to narrowing of the lactefferi or gland ducts, milk is not completely emptied or due to abnormalities in the nipples. The research design is descriptive with a sample of 50 people with the total sampling method. This research was conducted from April 2 to May 8, 2022. The instrument in this study was a questionnaire which included demographic data and a question. The results showed that most of the ASI dam mothers had sufficient knowledge of 40 people (80%) and those with less knowledge were 4 people (8%) and those who had good knowledge were 6 people (12%). ) in overcoming ASI dams in post partum mothers. From the results of this study regarding